Pemanfaatan Limbah Kulit Bawang Sebagai Pestisida dan Pupuk Organik - Intan Kurnia; Elika Br Gultom; Dini Afriyunita; Sukma Sakinah; Fefi Herninda; Rika Arnida; Fajar Bayu Lesmana; Cahaya Samudra; Mhd Dimas Fahdiansyah; M. Ejie Prasetyo; Rahmondia Nanda Setiadi (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The use of chemical pesticides in plant pest control is an easy and effective reason, although many have negative impacts on the environment. This can be a consideration for farmers in the use of organik pesticides that use materials available in nature to control plant-disturbing organisms, one of the organik pesticide ingredients used is onion skin and garlic, because they contain substances that are toxic to insects and fungi. Onion and garlic extracts can function as insect repellents. The activity of making organik pesticides is intended as a medicine for plants cultivated by farmers in Kota Lama Village, Indragiri Hulu District, Riau Province. Organik pesticides that are made are known to function in preventing insect pests on plants cultivated by local residents. The results of the pesticide have been applied to local residents' gardens. With the presence of pesticides and organik fertilizers, the people of Kota Lama Village feel very helpful because they can reduce costs for caring for plants. The use of pesticides and organik fertilizers is a new and much safer alternative for human health.